2022
DOI: 10.1186/s12967-022-03305-x
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0036412 affects the proliferation and cell cycle of hepatocellular carcinoma via hedgehog signaling pathway

Abstract: Background Hepatocellular carcinoma (HCC), as the most common type of liver cancer, is characterized by high recurrence and metastasis. Circular RNA (circRNA) circ_0036412 was selected for studying the underlying mechanisms of HCC. Methods Quantitative real time-polymerase chain reaction (qRT-PCR) and western blot analyzed gene and protein expression. Functional experiments evaluated HCC cell proliferation, apoptosis and cell cycle in vitro. In viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…It’s reported that circZNF609 sequestering microRNA-150 plays a role in promoting colorectal cancer progression by upregulating Gli1 expression [ 88 ]. Moreover, several circRNAs such as circSMO742 [ 89 ], circ-STAT3 [ 90 ], circ_0036412 [ 91 ] and circDCAF6 [ 92 ] could act as miRNA sponges to affect some cancer hallmarks.…”
Section: Introductionmentioning
confidence: 99%
“…It’s reported that circZNF609 sequestering microRNA-150 plays a role in promoting colorectal cancer progression by upregulating Gli1 expression [ 88 ]. Moreover, several circRNAs such as circSMO742 [ 89 ], circ-STAT3 [ 90 ], circ_0036412 [ 91 ] and circDCAF6 [ 92 ] could act as miRNA sponges to affect some cancer hallmarks.…”
Section: Introductionmentioning
confidence: 99%
“…42 Here, we demonstrated that circSLC39A5 was also down- Increasing evidence shows that circRNAs can play a key role in HCC proliferation, such as regulating stem cell characteristics, 43 affecting the expression of Ki67 and AFP, 44 and controlling tumor cell cycle arrest and cell senescence. [45][46][47] circRNAs can also affect the apoptosis of cancer cells and thus affect the programmed cell death of HCC, 48,49 or influence HCC invasion and metastasis by affecting the epithelial-to-mesenchymal transition (EMT). 50,51 Here, in vitro and in vivo experiments manifested that circSLC39A5 inhibited the proliferation, migration, and invasion of HCC cells, promoted cells apoptosis, and was associated with low expression of proliferation index Ki67 and capillarity marker CD34.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence shows that circRNAs can play a key role in HCC proliferation, such as regulating stem cell characteristics, 43 affecting the expression of Ki67 and AFP, 44 and controlling tumor cell cycle arrest and cell senescence 45–47 . circRNAs can also affect the apoptosis of cancer cells and thus affect the programmed cell death of HCC, 48,49 or influence HCC invasion and metastasis by affecting the epithelial‐to‐mesenchymal transition (EMT) 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of experiments have demonstrated that circRNAs can promote the development of HCC by regulating various signals involved with the cell cycle, proliferation, differentiation, cell survival and apoptosis, leading to abnormal activation of several molecules in signal transduction pathways [18] . Studies have con rmed that circRNAs can act via the AKT/ERK [19] , Wnt/βcatenin [20] , nuclear factor-kappa B [21], hedgehog [22] , c-Met [23] , JAK2/STAT3 [24] and other signalling pathways and are involved in the malignant biological behaviours of HCC. Recent studies have con rmed that circRNAs not only exert biological functions through the above signalling pathways but also affect the biological processes of HCC through other pathways.…”
Section: Discussionmentioning
confidence: 99%